Analisis Pengaruh Faktor Personal dan Faktor Organisasi terhadap Perilaku Tidak Selamat pada Pekerja Konstruksi - Irhandy, Gavin Andre; Erwandi, Dadan (National Journal of Occupational Health and Safety, 2022)
Construction industry has a high hazard and high risk to allow work accident. The purpose of this study was to analyze the effect of individual risk factor and organizational risk factor associated with unsafe behavior or substandard action in construction workers. This study used a cross sectional study design. The instrument used for collecting data and this research conducted in Mei – July 2021 involving 165 workers in the sports center stadium construction project Banten. The result of this research indicate age has a positive effect but not significant against unsafe behavior or substandard action. While education level, work experience in the project, average weekly working hours, safety motivation, organizational safety behavior have a negative effect but not significant against unsafe behavior or substandard action, and safety knowledge, psychological capital (self-efficacy, hope, resilience, and optimism) have a negative and significant effect against unsafe behavior or substandard action. Therefore, we need to control and intervene to reduce unsafe behavior or substandard action in workers.